ANALISIS PERILAKU ASSERTIVITAS SISWA KELAS XI SMK MUHAMMADIYAH I KABUPATEN KUBU RAYA TAHUN 2020 - Desi Kurniasih; Luhur Wicaksono; Ana Fergina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract Asertiveness, often referred to self-asertiveness is the behavior of people who agree or disagree to something. The present study aimed at analyzing assertivenessbehavior on students of grade XI of SMK Muhammadiyah 1 og Kubu Raya regency, The study was conducted in Muhammadiyah vocational school Number 1 (SMK) of kubu raya . The methodology employed in this research was descriptive using survey technique. The research had 44 students from grade XI SMK Muhammadiyah 1. The data was analyzed by using quantitative approach with indirect communication an inventory techniques. The findings showed assertiveness of studentsis most of SMK 1 Muhammadiyah is high although some indicators need to improve such as expressing their feeling to other making decision, and standing on their opinion. Keywords: Assertiveness, Behavior